2021
DOI: 10.1002/ima.22655
|View full text |Cite
|
Sign up to set email alerts
|

Electroencephalography based imagined alphabets classification using spatial and time‐domain features

Abstract: Imagined speech is a neuro-paradigm that can provide an alternative communication channel for patients in a locked-in syndrome state. We have performed an experiment in which a 32 channel industry-standard electroencephalography (EEG) device was used to record 26 imagined English alphabets from 13 subjects. We denoised the imagined signals by discrete wavelet transform and extracted the spatial filters by common spatial pattern method, and time-domain features. Spatial features when classified with linear supp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…In one of our previous works [20] on the SI data [28], the imagined vowels/a/and/u/were classified with a maximum average accuracy of 70% in the alpha band. In Agarwal and Kumar [36], an attempt to provide the frequency band for each individual imagined English alphabet in which it can be classified with the highest accuracy had been done. The results were inclined toward the alpha and theta bands.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In one of our previous works [20] on the SI data [28], the imagined vowels/a/and/u/were classified with a maximum average accuracy of 70% in the alpha band. In Agarwal and Kumar [36], an attempt to provide the frequency band for each individual imagined English alphabet in which it can be classified with the highest accuracy had been done. The results were inclined toward the alpha and theta bands.…”
Section: Discussionmentioning
confidence: 99%
“…The procedure of the experiment is shown in Figure 1. The authors have adopted a similar experimental paradigm in decoding imagined English alphabets [36]. The signals of the imagined words were recorded according to international 10–20 system placement of electrodes [37] by a 32 channel EEG device ‘Mobita’ produced by TMSi systems.…”
Section: Methodsmentioning
confidence: 99%
“…The first level DWT decomposes a signal into approximation coefficients (AC 1 ) and detail coefficients (DC 1 ), and further, at each subsequent level, the approximation coefficients (AC n ) are further divided into detail coefficients (DC n+1 ) and approximation coefficients (AC n+1 ). The order 4 Daubechies (db4) wavelet was used in the experiment because its smoothing property made it more suited to detecting changes in EEG signals [39] and also because research has suggested that the db4 wavelet basis is useful in imagined speech [18,19,40]. The DWT was employed at level 7 of signal decomposition using the db4 mother wavelet.…”
Section: Eeg Signal Processingmentioning
confidence: 99%
“…Varshney and Khan [18] experimented with the imagined speech EEG signals of six words using the discrete wavelet transform (DWT) to extract features and classify the signals using different models (RF and SVM) and obtained an average classification accuracy of 28.61%. Agarwal and Kumar [19] studied the use of DWT for denoise and CSP signal processing techniques to extract spatial characteristics from imagined speech of the twenty-six English alphabet EEG signals and classify the signals employing RF and SVM, obtaining a classification accuracy of 77.97%. Einizade et al [20], in the experiment decoding imagined speech of three words, exploited graph signal processing and graph learning-based signal characteristics of EEG signals to boost the effectiveness of SVM-based classifiers and achieved an accuracy of 50.10%.…”
Section: Introductionmentioning
confidence: 99%
“…The decomposition was computed by repeatedly filtering the discrete signals up to a predefined level. Earlier studies have demonstrated the effectiveness of utilizing Daubechies-4 (order 4) wavelet feature extraction for the classification of different types of EEG signals [38][39][40][41]. In this study, we applied the DWT using the Daubechies-4 wavelet with two-level decomposition on EPOC and the three-level decomposition on MUSE for denoising and information extraction.…”
Section: Eeg Signal Preprocessingmentioning
confidence: 99%